Lightering goods from a scow onto the beach, Nome, Alaska, approximately 1900. - Hegg, Eric A., 1867-1948 (1900)
Caption on image: "Lightering goods with derick Nome" Original photograph by Eric A. Hegg 1479; copied by Webster and Stevens 162.A